Prognostic Value of a Genetic Polymorphism in Promotor Region of AQP5 in Sepsis Depends on the Source of Infection - V. M. Pisarev; A. G. Chumachenko; I. N. Turin; R. A. Cherpakov; E. V. Elisina; E. K. Grigoriev; I. A. Aleksandrov; A. V. Tutelyan (Общая реаниматология)
Aquaporins represent proteins contributed to water transport through cell membrane. They are involved in formation and resolution of edema, cell migration and inﬂammatory reaction. There are only few studies linking the genetic polymorphism of aquaporin 5 (rs3759129 AQP5) and sepsis. At the same time, the apparent heterogeneity of patients along the foci of infection may limit ﬁnding the most signiﬁcant association of AQP5 genotypes with the course of infectious complications of critical conditions and restrict further development of rs3759129 AQP5 as a potentially strong marker of sepsis outcome.The purpose of the study was to determine whether the preferential localization of the infection aﬀects the prognostic value of the genetic marker AQP5 (1364A/C, rs3759129) in outcome prediction in sepsis (SEPSIS-3, 2016) patients.Materials and methods. Study groups (n=339) included ICU patients with abdominal sepsis (AS, including pancreatitits, peritonitis, cholecystitis, appendicitis; n=94) sepsis patients with other sources of infections  (n=65) and ICU patients without sepsis (n=180). AQP5 polymorphism was studied by analyzing PCR products in a 2% agarose gel using a AQP5 1364A/C speciﬁc tetra primer set.Result. Distribution of alleles (A and C) and genotypes (AA, AC and CC) AQP5 1364A/C in patients with  sepsis or sepsis subgroups (sepsis with no septic shock and sepsis shock patients) versus control group (healthy  volunteers) did not diﬀer. Although there was a trend to preferential survival of sepsis patients with genotype C AQP5 despite the source of infection, only patients with AQP5 CC or AC genotype and abdominal sepsis (Sepsis-3), or a subgroup of the same AQP5 genotype experiencing septic shock, demonstrated increased 30day survival versus AA homozygotic patients (P=0.002).Conclusion. The informative value of detecting the AQP5 CC or AC genotype for prognosis of 30-day survival versus AA homozygotic patients is most signiﬁcant only in abdominal sepsis patients.